Projection Precision of Right Foot Length and Fundus Uteri Height - Tuti Sukini; Siti Rofi’ah; Mohammad Hanafi (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2014)
The study is to determine the relationship between the length of the feet and the height of the fundus uterus. The research used the analytic survey with cross sectional approach. We used purposive sampling, and there were 30 respondents. Then we analized the test statistic using the Chi–Square. The results showed that p value 0.061 is greater than the significant level of 0.05 so that there is no accurate intersection of the projection of length in the measurement of the length of right foot and the height of fundus uterus in third trimester pregnant women with pelvic narrowness incident. As a provider of antenatal care, Midwives should always assume that all pregnant women have the same risk and treating all pregnant women equally, due to the measurement of the height of the fundus that is projected from the lengths of the right foot can not be used as a prediction of narrow pelvis.